Training Program for Gaining Cultural Elements with Drama and Art Activities: My Culture, My Identity - YÜKSEL, MÜGE (My University, 2020)
The purpose of the research is to enable children born and raised in Germany with different cultural backgrounds to compare, internalize, and adopt the cultural characteristics of both themselves and their friends through a training program developed and enriched with drama and art activities. Hence, the developed training program is expected to support children’s healthy identity development and self-expression skills. The study has been carried out using the qualitative research design of applied action research. The study group consists of eight children between the ages of five and six years old: five of Turkish, one of German, one of Moroccan, and one of Danish origin, all of whom are receiving education in Berlin at a preschool for children of all backgrounds. An eight-session training program has been implemented with these children. Before implementing the training, a pre-study was carried out with the classroom teachers and families with additional parental meetings being held at the end of each session to support the work with families. At the end of the study, the implemented training program was found to have improved the children’s awareness of their cultural characteristics, increased their expression skills, and encouraged them to cooperate and work in harmony with groups.

Bu araştırmada amaç, Almanya’da doğup büyüyen farklı kültürel kökenlere sahip çocukların hem kendi hem de diğer arkadaşlarının kültürel özelliklerini, drama ve sanat etkinlikleriyle zenginleştirilmiş bir eğitim programıyla karşılaştırmalarını, içselleştirmelerini ve benimsemelerini sağlamaktır. Bu yolla kimlik gelişimlerini ve kendini ifade etme becerilerini sağlıklı bir şekilde desteklemek beklenmektedir. Çalışma, nitel araştırma türlerinden uygulamalı eylem araştırması deseni ile yürütülmüştür. Çalışma grubunu Berlin’de farklı kültürden çocukların eğitim aldığı bir okul öncesi eğitim kurumuna devam eden 5-6 yaş grubu beş Türk, 1 Alman, 1 Fas, 1 Danimarka asıllı olmak üzere toplam 8 çocuk oluşturmuştur. Bu çocuklarla sekiz oturumluk, eğitim programı uygulanmıştır. Uygulamalar öncesi sınıf öğretmeni ve ailelerle çalışılmış, her oturumun sonunda ailelerle yapılan çalışmaları desteklemeye yönelik toplantılar gerçekleştirilmiştir. Çalışmadan sonunda, uygulanan eğitim programının çocukların kültürel özelliklerine ilişkin farkındalıklarını geliştirdiği, ifade becerilerini arttırdığı, grup halinde işbirliği ve uyum içerisinde hareket etmelerini desteklediği sonucuna varılmıştır._x000D_
Drama ve Sanat Etkinlikleriyle Kültürel Ögeleri Kazandırma Programı: Kültürüm Kimliğim